A Improving the Competence of Village Officials in Preparing Village Budget Plans - Sukmawati Yuniar, Latifah; Amir, Andi Mattulada; Pattawe, Abdul; Indriasari, Rahayu; Jurana N.S; Nurhaja Djasman; Shidq Dhiyaurrahman Ahmad; Selvi (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2026)
Banggai Islands Regency is a popular tourist destination for both domestic and international tourists due to the beauty of Lake Paisupok. To support tourism activities and improve the local economy, government support, particularly from the local village government, is essential. Therefore, education is needed for village officials in the village budget preparation process. The purpose of this community service activity is to educate village officials in the process of preparing the village budget by paying attention to the priority plan of activities in the village fund program for the community and village government officials. The method used is presentation, questions and answers, and discussions on understanding the preparation of priority plans for activities in the village fund program. The community service activities that have been implemented ultimately provide an understanding of the preparation of priority plans for activities in the village fund program for the community and village government officials so that the management of village funds can be carried out in an orderly manner, in accordance with the provisions of laws and regulations, efficiently, economically, effectively, transparently, and responsibly by paying attention to the sense of justice and propriety and prioritizing the interests of the local community.